2004
DOI: 10.1016/s1476-5586(04)80047-2
|View full text |Cite
|
Sign up to set email alerts
|

ONCOMINE: A Cancer Microarray Database and Integrated Data-Mining Platform

Abstract: DNA microarray technology has led to an explosion of oncogenomic analyses, generating a wealth of data and uncovering the complex gene expression patterns of cancer. Unfortunately, due to the lack of a unifying bioinformatic resource, the majority of these data sit stagnant and disjointed following publication, massively underutilized by the cancer research community. Here, we present ONCOMINE, a cancer microarray database and web-based data-mining platform aimed at facilitating discovery from genome-wide expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

80
3,049
2
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 3,261 publications
(3,132 citation statements)
references
References 40 publications
80
3,049
2
1
Order By: Relevance
“…RSU1 was originally identified in a screen for genes that could inhibit Ras-mediated signaling 29 and was later shown to inhibit anchorage-independent growth of MCF7 breast cancer cells 30 . Notably, we have observed that RSU1 is consistently downregulated in prostate cancer 3,24,26 , further suggesting a tumor suppressor role for this gene; however, to date, the mechanism by which RSU1 exerts its effects has not been elucidated. Here our model predicted, and we experimentally confirmed that RSU1 interacts with LIMS1, an adaptor protein involved in integrin signaling at focal adhesions 31 .…”
Section: A N a Ly S I Smentioning
confidence: 88%
See 3 more Smart Citations
“…RSU1 was originally identified in a screen for genes that could inhibit Ras-mediated signaling 29 and was later shown to inhibit anchorage-independent growth of MCF7 breast cancer cells 30 . Notably, we have observed that RSU1 is consistently downregulated in prostate cancer 3,24,26 , further suggesting a tumor suppressor role for this gene; however, to date, the mechanism by which RSU1 exerts its effects has not been elucidated. Here our model predicted, and we experimentally confirmed that RSU1 interacts with LIMS1, an adaptor protein involved in integrin signaling at focal adhesions 31 .…”
Section: A N a Ly S I Smentioning
confidence: 88%
“…We identified coexpressed genes from 65 genome-wide gene expression data sets present in the Oncomine Cancer Microarray Database 3,21 . The 65 data sets consisted of more than 5,000 diverse microarray profiles representing many tissue types, differentiation states and cellular compositions, thus covering a broad spectrum of gene expression (Supplementary Table 2).…”
Section: Gene Expressionmentioning
confidence: 99%
See 2 more Smart Citations
“…We used the breast cancer data sets included in Oncomine [16] unique FEVS-exclusive genes, most of which were identified by Oncomine as highly significantly associated with grade in at least one of the independent data sets (Table S1). …”
Section: An Application To Microarray Data From Breast Cancermentioning
confidence: 99%